Parents' perspectives towards sexual and reproductive health and rights education among adolescents in Jordan: content, timing and preferred sources of information. Issue 5 (3rd September 2022) - Othman, Areej; Abuidhail, Jamila; Shaheen, Abeer; Langer, Ana; Gausman, Jewel
ABSTRACT: Young people require good quality information about their sexual and reproductive health and rights (SRHR) while transitioning to adulthood and parents have a key role in providing it. This study intended explored Jordanian and Syrian parents' perspectives on initiating discussions about SRHR with their children. A convenience sample of Jordanian and Syrian parents of young people aged 15–19 years old was recruited from local community centres in four cities in Jordan. Data were collected through 20 focus groups and analysed using iterative thematic coding. Four main themes were developed: 'SRHR awareness starts at home', 'Tell them everything … . but "about sex, no"', 'Engagement or marriage is the gateway to education about sexual intercourse, and 'Credible sources of SRH information: schools, not peers'. Parents felt motivated to initiate sensitive discussions with their children and were supportive of the introduction of sexual health education into the school curriculum. Creative approaches to overcoming cultural sensitivities were preferred, for example preparing young people for a healthy marital life, rather than an explicit focus on sexual health education.